Pendidikan Agama Kristen dan Pancasila: Upaya Membangun Kesadaran Multikultural Generasi Muda di Indonesia - Eddy Tjondro; Imanuel Catur Oktanto Suryoadi; Kissinger Situmeang; Linda Bustan (Sekolah Tinggi Teologi Injili Efrata Sidoarjo, 2025)
The rise of intolerance among Indonesian youth reflects a gap that requires the integration of faith teaching and the values of Pancasila. This study employs a descriptive qualitative approach with an analysis of recent literature. The findings indicate that Christian Religious Education has significant potential to internalize Pancasila values through three main implementation strategies, namely: curriculum integration, contextual teaching methods, and the formation of multicultural character. Christian Religious Education and Pancasila are not opposing entities, but rather two sources of values that can mutually enrich one another. The integration of both, through appropriate pedagogical strategies, makes a significant contribution to shaping Christian youth who are steadfast in faith, virtuous in character, and prepared to become agents of unity in the midst of Indonesia’s diversity.